LITERATURE REVIEW: MENJADI PRECEPTOR YANG BAIK PADA PROGRAM PRECEPTORSHIP PERAWAT BARU (Literature Review: Be a Good Preceptor in Preceptorship Program for Novice Nurse) - Mare, Agustina Chriswinda Bura; Dwidiyanti, Meidiana (JURNAL NERS LENTERA, 2018)
Background: The transition of roles has faced by novice nurses from new students to professional nurses can be stressful when adapting the roles. Preceptorship program in hospitals are facilitated the new nurses as a guidance by preceptor to orientation, socialization and recruitment staff program. To run an effective preceptorship program requires a good preceptor. Purpose: The purspose of this article is to know the ways to be a good preceptor for preceptorship program easily applied in the hospital. Methods: The articles were found through Google search, CINAHL with keywords preceptorship, nursing, novice nursing. Results and conclusions: 7 skills are required to be a good preceptor. Training for preceptor is also needed by preceptor to know how the preceptorship program can work effectively.